The teacher's influence on the athletes' value system in the context of the formation of a socially acceptable course of action - Skok N.S. ,; Baryaev A.A. ,; Kulikov V.S. ,; Ulitskaya T.I. , (Theory and Practice of Physical Culture, 2025)
Objective of the study. This study is aimed at studying the potential of pedagogical influence on the formation of a value system among athletes of the sports reserve (hereinafter referred to as athletes) in the context of their training in socially acceptable behavior. Methods and structure of the study. The methodologyandorganization of the studyincludedananalysis of existingworksonvalueorientationsandsociallyappropriatebehaviorinsports. A survey of athletes was alsoused,apedagogicalexperiment was conducted, a correlationanalysis was performed, and the dataobtained were interpretedandsystematized(n=14;sports:orienteering,handball,volleyball,sailing, and rowing;agegroup:14-17years). The study examines the possibilities of pedagogical influence on the formation of value orientations in order to prevent and correct deviant behavior in athletes and the formation of socially acceptable behavioral models in them. The task of analyzing the development of the athletes' value system has been clarified. Positive changes in terminal values have been recorded, reflecting the desire for professional (interesting work/study) and personal self-realization (happy family life, love and spiritual intimacy). There are also positive trends in the development of instrumental values, both individualistic (independence, willpower) and conformist (self-control). Results and conclusions. It has been established that the prevention and correction of deviant behavior have a positive effect on the formation of athletes' value orientations. The relationship between the formation and manifestation of socially adequate behaviors in athletes and their age, level of athletic training, as well as the type of sport was found. The possibility of correcting deviant behavior and developing socially acceptable behavior through pedagogical tools and methods has been confirmed.